Optimal obstacle control problem - 朱砾 李秀华 郭兴明 (Applied mathematics and mechanics, 2008)
In the paper we discuss some properties of the state operators of the optimal obstacle control problem for elliptic variational inequality.Existence,uniqueness and regularity of the optimal control,problem are established.In addition,the approximation of the optimal obstacle problem is also studied.